Wearable Sensors for Monitoring Vital Signs of Patients - Kaur, Parminder; Singh Saini, Hardeep; Kaur, Bikrampal (International Journal of Engineering and Technology, 2018)
Vital signs of a person are the indicator of basic bodily functions and provide critical information for accessing a patient's state of health. The four Vital signs are: Blood Pressure, Pulse Rate, Body temperature and Respiration Rate. In some cases, blood oxygen saturation is also measured. Vital signs help in identifying an already existing medical condition, diagnosing new disease and can also be very helpful in providing critical care to patients in time of emergency. Traditional ways of Vital sign monitoring are being replaced by more technical methods employing the use of wearable sensors. Not only are wearable sensors an aid for getting vital signs accurately but a multitude of parameters can be obtained by using an assembly of wearable sensors. With the help of wearable sensors, telemonitoring of patients has become a reality. This paper discusses the Vital parameters, their normal ranges and different wearable sensors to measure these parameters.Â Â